Interleukin-10: A double-edged sword in breast cancer - Chun-Ming Chang; Ho Yin Pekkle Lam; Hao-Jen Hsu; Shinn-Jong Jiang (Tzu Chi Medical Journal)
Breast cancer (BC) is a frequently diagnosed cancer among women worldwide. Currently, BC can be divided into different subgroups according to the presence of the following hormone receptors: estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2. Each of these subgroups has different treatment strategies. However, the presence of new metastatic lesions and patient deterioration suggest resistance to a given treatment. Various lines of evidence had shown that cytokines are one of the important mediators of tumor growth, invasion, metastasis, and treatment resistance. Interleukin-10 (IL-10) is an immunoregulatory cytokine, and acts as a poor prognostic marker in many cancers. The anti-inflammatory IL-10 blocks certain effects of inflammatory cytokines. It also antagonizes the co-stimulatory molecules on the antigen-presenting cells. Here, we review the current knowledge on the function and molecular mechanism of IL-10, and recent findings on how IL-10 contributes to the progression of BC.